Estudo da sensação térmica e definição de limites de conforto para espaços abertos na cidade de Fortaleza, CE - Petalas, Kety Vasconcelos (2015)
Human termofisiológicas reactions to climatic conditions are commonly evaluated from the application of thermal comfort indices. Results are interpreted by assessment scales defined by the relationship between the calculated value and the thermal sensation reported by people adapted to the temperate climate. However, many studies have identified a gap between these answers and pointed to the need for adjustments. Fortaleza is a coastal city of hot and humid tropical climate, Naturally stressful due to heat. On one hand, it presents significant climate change and, second, few studies have evaluated the impact of these changes in thermal sensation of the population. Thus, this study aims to verify the applicability of some thermal indices and set new limits of comfort that can be applied in bioclimatic analysis of public open spaces in the city. Initially, with the aim of identify the thermal perception and preference of the population and collect information necessary for the calculation of the indices, measurements questionnaires were administered and conducted in field representative days of the four seasons between 2011 and 2012, from 09:00 to 16: 00h. The sample was selected by convenience and considered the adult population, healthy and acclimatized to the local climate. The thermal indices were calculated individually and all information were statistically treated from chiquadrado test, analysis of variance and probit regression analysis. The results show higher comfort boundaries and decrease in amplitude of the tracks, identifying one greater heat tolerance according to the adaptive approach. They also reveal the perception climate as slightly warm to hot, the preference of the population for environment cooler thermal and indicate the need to preserve the shading and ventilation provided, respectively, for afforestation and by sea breezes and regional wind. Looking at the period 1980-2010, it is observed that although most situaremse data between the new limits of comfort, there is evidence of a warmer wind chill. The defining new comfort ranges provides subsidies to urban planners in the process decision-making, allowing a better assessment of open spaces, the comparison of different urban solutions and interventions more consistent with the local climate.